The Mediating Role of School Belonging and Parental Educational Aspirations in the Relationship Between Goal Congruence and Academic Persistence - Ataei Dizaji, Samira; Moradi, Shokoufeh; Khodadadi, Azad; Memari, Sara (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to examine the mediating role of school belonging and parental educational aspirations in the relationship between goal congruence and academic persistence among high school students. Methods and Materials: This study employed a quantitative, cross-sectional correlational design using structural equation modeling. The statistical population consisted of high school students in Tehran during the 2025 academic year, from which a sample of 412 students (209 females and 203 males) was selected through multistage cluster sampling. Data were collected using standardized instruments, including the Goal Congruence Scale, the Psychological Sense of School Membership Scale, the Parental Educational Aspirations Scale, and the Academic Persistence Scale. The validity and reliability of all instruments had been confirmed in previous studies. Data analysis was conducted using SPSS-27 for preliminary analyses and AMOS for structural equation modeling. Model fit was evaluated using indices such as χ²/df, CFI, TLI, NFI, and RMSEA, and mediation effects were tested using bootstrapping procedures. Findings: The results indicated that goal congruence had a significant direct effect on academic persistence (β = 0.29, p < 0.001). Additionally, goal congruence significantly predicted school belonging (β = 0.51, p < 0.001) and parental educational aspirations (β = 0.43, p < 0.001), both of which had significant positive effects on academic persistence (β = 0.34 and β = 0.21, respectively; p < 0.001). Bootstrapping analysis confirmed that both school belonging (β = 0.17, 95% CI [0.11, 0.24]) and parental educational aspirations (β = 0.09, 95% CI [0.05, 0.14]) significantly mediated the relationship between goal congruence and academic persistence, with school belonging demonstrating a stronger mediating effect. The overall model demonstrated good fit to the data (χ²/df = 2.41, CFI = 0.93, TLI = 0.92, NFI = 0.91, RMSEA = 0.058). Conclusion: The findings highlight the critical role of both individual motivational alignment and relational-contextual factors in shaping academic persistence.